Safety, Efficacy of an Accelerated Regimen of Low-Dose Recombinant Tissue-Type Plasminogen Activator for Reperfusion Therapy of Acute Pulmonary Embolism. (September 2021) - Hoang, Bui Hai; Do, Phuc Giang; Le, Lac Duy; Bui, Thao Thi Huong; Bui, Thinh Nghia; Nguyen, Quan Minh; To, Duong Hoang; Nguyen, Anh Dat; Dinh, Michael M.; Goldhaber, Samuel Z.; Day, Richard; Nguyen, Hieu Lan
Controversy persists regarding the safety and efficacy of an accelerated low-dose recombinant tissue-type plasminogen activator (rt-PA) regimen for reperfusion therapy in acute pulmonary embolism. This study describes the outcomes of an accelerated low-dose rt-PA regimen for the treatment of acute pulmonary embolism in Vietnamese patients. This was a case series from October 2014 to October 2020 from 9 hospitals across Vietnam. Patients presenting with acute pulmonary embolism with high to intermediate mortality risk were administered alteplase 0.6 mg per kilogram (maximum of 50 mg) over 15 min. The main outcomes were the proportion who survived to hospital discharge and at 3 months as well as in-hospital hemorrhage (major and minor according to International Society of Thrombosis and Hemhorrage definitions). A total of 80 patients were enrolled: 48 (60%) with high risk for mortality and 32 patients (40%) with intermediate risk for mortality. A total of 7 (8.8%) died in hospital. All deaths occurred in the high-risk mortality group. The 73 patients who were discharged alive remained alive at 3 months follow up. During hospitalization, 1 patient (1.3%) suffered major bleeding, and 7 (8.8%) had minor bleeding. An accelerated thrombolytic regimen with alteplase 0.6 mg/kg (maximum of 50 mg) over 15 min for acute pulmonary embolism appeared be effective and safe in a case series of Vietnamese patients.